The Effectiveness of the Problem Based Flipped Classroom Model with E-Modules in Improving Critical Thinking Skills of Pre-Service Physics Teachers - Sutrio, Sutrio; Busyairi, Ahmad; Doyan, Aris; Kosim, Kosim; Hikmawati, Hikmawati (Department of Physics Education, Universitas Mataram, 2023)
Critical thinking skills are one of four skills that students must have in the 21st century. However, several research results show that students' critical thinking skills in Indonesia are still very low. This research aims to test the effectiveness of the Problem-Based Flipped Classroom (PBFC) model assisted by e-Modules in improving the critical thinking skills of prospective physics teachers. This type of research is quasi-experimental with a non-equivalent control group design. The research was conducted at the Physics Education Study Program at the University of Mataram. The research subjects consisted of 52 prospective physics teachers who were studying Basic Physics I. Data was collected using a critical thinking skills test given before and after treatment. The results of data analysis show that the average score of critical thinking skills of prospective physics teachers in the experimental class and control class both increased to the moderate category with N-Gain scores of 0.63 and 0.48 respectively. Based on the results of the t-test at the 95% confidence level with the degree of freedom dk= 52 it shows that there is a significant difference in the increase in Critical Thinking Skills between the experimental class and the control class with a value of tcount= 2.21 with a value of ttable = 2.01 . Apart from that, based on the results of the effect size calculation, it shows that the effectiveness of the E-Module assisted PBFC model in improving students' critical thinking skills relative to the conventional model is different in the large category. In other words, the PBFC model assisted by e-modules can be used as an alternative learning in the classroom to improve the critical thinking skills of prospective physics teachers or students in general.